Proyecto de factibilidad para la implementación de una empresa comercializadora de cocinas de inducción para la ciudad de Loja - Tinoco Blacio, Judith María (2015)
This paper's main objective: PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF a marketer of induction cookers NOW FOR THE CITY OF LOJA that corresponds to a business idea or initiative has certain stages of marketing for the launch of the company. To this have been taken into account a set of resources, human, material, technological and others that allowed establishing whether the project is viable or not. With the use of deductive, analytical, mathematical and statistical methods and by applying the techniques of observation and survey, it was possible to conduct different studies containing this project as they are Market Research, Technical Study, Organizational Study and Financial Study. For the following investigation to the total population of the city of Loja was taken, according to the National Institute of Statistics and Census, by the 2010 census and population projection 180 581 inhabitants, whose sample size for this project was carried out a total survey of 381 families in the city of Loja. The market study aims to determine the unmet demand of 2,297 for the first year, which was there for the marketing of induction cookers on the market. The technical study, determined that the company will have an installed capacity of 1,080 induction cookers a year as full capacity, which represents 47.01% of the unmet demand for marketing and capacity utilization of 90% for the first year of life the project will guide the undertaking of the company in the city of Loja. Subsequently, the legal structure of the company whose corporate name was designed Company Trading Company "INDUC-LOJA" Limited Company called (Cia. Ltda.), Which will be located in the center of the city of Loja, on 18th Street November between Azuay and Market, in which fundamental in the operation and the good organization of the company hierarchies defined, such as: General Assembly of Members, a Manager, a secretary Contadora, a sales manager and a driver seller. The Economic and Financial Study identified that the areas of investment needed for the implementation of the project are Fixed Assets, and Deferred Assets Current assets is $ 34.708,91 US dollars and once known the amount of investment is necessary to find funding sources and for this we will consider two sources that is the equity of 56,78% which is the capital of the PARTNERS = 19.708,91 Dollars and debt capital of 43,22% which is a LOAN = 15,000.00 Dollars. Financial evaluation determined the project's viability by the financial indicators: the Net Present Value is 151,314.38; Relationship (Benefit / Cost) is 1.20, meaning that for every dollar spent earns 20 cents; the Capital Recovery Period is 1 year and 8monthsand 8 days; Internal Rate of Return is the 69,01% Sensitivity Analysis and in increasing costs is 5,69% and the decrease in earnings is 5,17%. Finally they came to the conclusions and recommendations which must be to translate this study